2019
DOI: 10.3389/fcimb.2019.00295
|View full text |Cite
|
Sign up to set email alerts
|

Production of Membrane Vesicles by Enterococcus faecium Cultured With or Without Subinhibitory Concentrations of Antibiotics and Their Pathological Effects on Epithelial Cells

Abstract: Enterococcus faecium is a clinically important pathogen associated with opportunistic infection and multi-drug resistance. E. faecium has been shown to produce membrane vesicles (MVs), but MV production by E. faecium under antibiotic stress conditions and the pathogenic traits thereof have yet to be determined. This study investigated the production of MVs in E. faecium ATCC 700221 cultured with sub-minimum inhibitory concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 56 publications
(84 reference statements)
4
14
0
Order By: Relevance
“…Nutrient limitation and antibiotics is furthermore known to increase vesiculation (Toyofuku et al, 2019 ). Subinhibitory concentrations of the last resort anti-staphylococcal antibiotic, vancomycin, has been shown to influence physiology, growth and toxin production by S. aureus (Hsu et al, 2011 ; Cafiso et al, 2012 ; He et al, 2017 ), and has been found to increase EV production in another Gram-positive species, Enterococcus faecium (Kim et al, 2019 ). Hence, in this study, we used iron-chelated media supplemented with vancomycin to evaluate whether the EVs produced by S. aureus MSSA476 are associated with sRNAs when grown in conditions that mimic an infection that is being treated with an antibiotic.…”
Section: Introductionmentioning
confidence: 99%
“…Nutrient limitation and antibiotics is furthermore known to increase vesiculation (Toyofuku et al, 2019 ). Subinhibitory concentrations of the last resort anti-staphylococcal antibiotic, vancomycin, has been shown to influence physiology, growth and toxin production by S. aureus (Hsu et al, 2011 ; Cafiso et al, 2012 ; He et al, 2017 ), and has been found to increase EV production in another Gram-positive species, Enterococcus faecium (Kim et al, 2019 ). Hence, in this study, we used iron-chelated media supplemented with vancomycin to evaluate whether the EVs produced by S. aureus MSSA476 are associated with sRNAs when grown in conditions that mimic an infection that is being treated with an antibiotic.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 5 C, MV TSB treated with proteinase K significantly inhibited the expression of IL-1β , TNF-α , and IL-8 genes as compared to intact MVs. Treatment of MVs derived from Enterococcus faecium with proteinase K also significantly reduced the expression of pro-inflammatory cytokine and chemokine genes in Caco-2 cells as compared to treatment with intact MVs [ 27 ]. These findings suggest that proteins in the surface or lumens of L. monocytogenes MVs are largely responsible for pro-inflammatory responses in host cells.…”
Section: Discussionmentioning
confidence: 99%
“…(Wagner, Joshi et al 2018) Drug resistance transporter EmrB and tellurite resistance protein TelA are also commonly present in MVs from E1162 and MVs from strain ATCC 700221. (Kim, Kim et al 2019) The presence of glycopeptide resistance-related protein such as VanR-A, VanS-A was observed in previous study on the MVs from E155 strain (Wagner, Joshi et al 2018), but these proteins are not present in the MVs from E1162 strain. This is logical as E1162 is a vancomycin-sensitive strain and four strains used in previous study are vancomycin-resistant.…”
Section: Discussionmentioning
confidence: 78%
“…The observation of proinflammatory cytokine increase is also seen in a previous study by Kim et.al, in which it was reported that MVs from E. faecium can induce strong proinflammatory response in host cells. (Kim, Kim et al 2019) From a manufacture point of view, we provide culture and isolation methods which allows the harvest of clean, and quality-controllable MV products. As the gradientultracentrifugation isolation procedures may be difficult to be used for large volume of culture medium, further work towards rapid and time-effective, cost-effective methods should therefore be considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation